HUBUNGAN PEMBELAJARAN AQIDAH AKHLAK DENGAN AKHLAK SISWA KELAS VIII DI MTs DARUL AMIEN JAJAG GAMBIRAN BANYUWANGI - Fauzi, Anis; Khotimah, Khusnul (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to find out the relationship of learning aqidah akhlak with the morals of grade VIII students in MTs Darul Amien Jajag Gambiran School Year 2020/2021 and to know the extent of the relationship of learning aqidah akhlak with the morality of grade VIII students in MTs Darul Amien Jajag Gambiran School Year 2020/2021. This study uses a quantitative approach with a type of quantitative correlation research. The population in this study was all grade VIII students who numbered 45 students. Of these populations sampling using saturated sample techniques, due to the number of students is less than 100. In the process of collecting data, namely using passive participation observation methods, interview methods, questionnaire methods, and documentation methods. Measurement of learning aqidah akhlak using the daily test value of students and the question of questionnaire statement for the morality of students using validity test and reliability test. Data analysis techniques using Chi Square. From the test result the validity of 10 question items is declared valid because r-count > r-table with a significance level of 0.05. While from the reliability test results 10 questions are declared reliable because the value of cronbach's alpha > 0.60. The results of this study showed Chi Square count = 18,701 and Chi Square table = 3,841 then obtained r-count > r- table or 18,701 > 3,841. Thus Ho was rejected and Ha accepted, so it can be concluded that there is a relationship of learning aqidah akhlak with the morality of grade VIII students in MTs Darul Amien Jajag Gambiran School Year 2020/2021. Next to find out the extent of the relationship using the chi square contingency coefficient formula with the help of SPSS Version 16.0 is 0.542 and if included in the conversion value belongs to the moderate category.